A preparation method of multi-element doped silicon-based composite material and silicon-based composite material thereof
By doping rare earths and catalysts in porous silicon and coating nitrogen and carbon sources through vapor deposition, the problems of poor electronic conductivity and low first-time efficiency of silicon-based composite materials in lithium-ion batteries are solved, and the material is realized High electronic conductivity and good cycling performance.
Patent Information
- Application Number
- CN202211227625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-10-09
AI Technical Summary
Existing silicon-based composite materials have problems of poor electronic conductivity and low first-time efficiency in lithium-ion batteries, which affect their power performance and cycle life.
Doping rare earths and catalysts into porous silicon through hydrothermal reactions to form a rare earth-doped silicon-based material precursor, and then deposition and coating the nitrogen and carbon sources on their surfaces through vapor deposition to enhance the electronic conductivity and circulation of the material. performance.
It significantly improves the electronic conductivity and cycling performance of silicon-based composite materials, and improves the power performance and energy density of lithium-ion batteries.
Smart Images

Figure CN115498163B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery preparation, and specifically relates to a preparation method of a multi-element doped silicon-based composite material and the silicon-based composite material. Background Art
[0002] Silicon-carbon materials are energy storage materials, in which silicon is an active substance that provides lithium storage capacity; carbon is a dispersed matrix that buffers the volume change of silicon particles when lithium is inserted and removed, maintains the integrity of the electrode structure, and maintains the electrical contact inside the electrode. Therefore, silicon-based composite materials combine the advantages of both, showing high specific capacity and long cycle life, and are expected to replace graphite as a new generation of lithium-ion battery negative electrode materials.
[0003] However, silicon-carbon materials have poor electronic conductivity that affects their power performance, and their low first efficiency affects the energy density of the entire battery. The main technical means to improve the power of materials and their first efficiency in the prior art include doping, coating and alloying of materials. For example, the invention patent with the authorized patent number CN111048770B discloses a ternary doped silicon-based composite material and its preparation method and application. Its composite negative electrode material includes silicon, silicon oxide, dopants and their silicates, and a carbon coating layer. The silicates and doped element oxides are evenly distributed in the silicon oxide substrate to form a uniform composite structure. The carbon material coating layer is evenly coated on the surface of the composite structure to improve the first efficiency of the material and its cycle performance. The first doping element and the second doping element are physically mixed, with poor consistency and poor bonding between the materials, and the effect of improving the rate and expansion performance of the material is very limited.
[0004] Based on the above situation, the applicant decided to seek technical solutions to solve the above technical problems based on the inventor's many years of dedicated research experience in the fields of silicon-based materials and lithium-ion batteries. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for preparing a multi-element doped silicon-based composite material and a silicon-based composite material thereof, which significantly improves the electronic conductivity of the silicon-based composite material and improves the cycle performance of lithium-ion batteries used therein.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a multi-element doped silicon-based composite material comprises doping rare earth and a catalyst into porous silicon through a hydrothermal reaction to obtain a rare earth doped silicon-based material precursor as a core; and then depositing a nitrogen source and a carbon source on the surface of the rare earth doped silicon-based material precursor through a vapor deposition method.
[0008] Preferably, the steps of preparing the rare earth-doped silicon-based material precursor include:
[0009] S10), etching the surface of the silicon alloy with acid vapor to obtain porous silicon;
[0010] S20), mixing the porous silicon obtained in the above step S10) with a rare earth carbonate aqueous solution and a catalyst aqueous solution to obtain a porous silicon-rare earth-catalyst mixture, wherein the weight ratio of rare earth carbonate: catalyst: porous silicon is in the range of 1-5:1-5:100;
[0011] S30), subjecting the porous silicon-rare earth-catalyst mixture to a hydrothermal reaction under heating and pressurization conditions to obtain the rare earth-doped silicon-based material precursor.
[0012] Preferably, in the step S10), the silicon alloy is selected from one of aluminum silicon alloy, magnesium silicon alloy, nickel silicon alloy, titanium silicon alloy, tungsten silicon alloy or a mixture of any of them, wherein the silicon content in the silicon alloy is not less than 60wt%; the acid vapor is hydrofluoric acid vapor, and the etching time is not less than 1 hour.
[0013] Preferably, in step S20), the weight percentage of rare earth carbonate in the rare earth carbonate aqueous solution is not less than 0.5wt%; the rare earth carbonate is selected from one of lanthanum carbonate, cerium carbonate, yttrium carbonate, praseodymium carbonate, or a mixture of any of them.
[0014] Preferably, in the step S20), the weight percentage of the catalyst in the catalyst aqueous solution is not less than 0.5wt%; the catalyst is selected from one of ferric chloride, cobalt chloride, nickel chloride or a mixture of any of them.
[0015] Preferably, in the step S20), the porous silicon-rare earth-catalyst mixture is further added with melamine in an amount not less than 0.2 wt % by weight, and is evenly dispersed by ultrasonication.
[0016] Preferably, in the step S30), the heating and pressurizing conditions are set to: react at a temperature range of 100-250°C and a pressure range of 1-5Mpa for at least 1 hour, and after the hydrothermal reaction is completed, the reaction product is filtered and freeze-dried to obtain the rare earth-doped silicon-based material precursor.
[0017] Preferably, the nitrogen source and the carbon source are deposited and coated sequentially or simultaneously by a vapor deposition method.
[0018] Preferably, the nitrogen source is 3-aminopropyltriethoxysilane gas, which is kept warm at a temperature range of 900-1300°C for at least 1 hour, and the 3-aminopropyltriethoxysilane gas undergoes a cracking reaction, so that the surface of the rare earth-doped silicon-based material precursor is deposited and coated with the nitrogen source; and / or the carbon source is carbon source gas, which is kept warm at a temperature range of 700-1100°C for at least 1 hour.
[0019] Preferably, a multi-element doped silicon-based composite material is obtained by the preparation method as described above.
[0020] It should be noted that the silicon alloy involved in the present application refers to silicon alloy particles with a diameter not greater than 80 microns, which can be purchased directly from the market.
[0021] The present invention relies on hydrothermal reaction to dope rare earth and catalyst in the pores of porous silicon. On the one hand, the doped rare earth compound has high electronic conductivity and stable structure, and after being combined with silicon material, it can significantly improve the electronic conductivity and surface electronic state of the material, reduce its internal resistance, and improve its rate performance; on the other hand, the doped catalyst provides a matrix for subsequent carbon source deposition, which is convenient for the carbon source to grow amorphous carbon with a vertical structure on its surface; at the same time, the present application also uses a vapor deposition method to crack 3-aminopropyltriethoxysilane as a nitrogen source to generate free radical silicon, so that the nitrogen source coating is stably and reliably deposited on the surface of the silicon-based material as the core to improve its density, and because the rare earth compound is coated in the core of the material, the electronic conductivity of the multi-element doped silicon-based composite material is further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM picture of the multi-element doped silicon-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] This embodiment discloses a method for preparing a multi-element doped silicon-based composite material, in which rare earths and catalysts are doped into porous silicon through a hydrothermal reaction to obtain a rare earth-doped silicon-based material precursor as a core; then a nitrogen source and a carbon source are deposited and coated on the surface of the rare earth-doped silicon-based material precursor through a vapor deposition method.
[0024] Preferably, in this embodiment, the steps of preparing the rare earth-doped silicon-based material precursor include:
[0025] S10), using acid vapor to etch the surface of the silicon alloy to obtain porous silicon; preferably, in this step S10), the silicon alloy is selected from one of aluminum silicon alloy, magnesium silicon alloy, nickel silicon alloy, titanium silicon alloy, tungsten silicon alloy or a mixture of any of them, wherein the silicon content in the silicon alloy is not less than 60wt%, preferably 60-90wt%; the acid vapor is hydrofluoric acid vapor, and the etching time is not less than 1 hour, preferably 1-12 hours;
[0026] S20), the porous silicon obtained in the above step S10) is mixed evenly with a rare earth carbonate aqueous solution and a catalyst aqueous solution to obtain a porous silicon-rare earth-catalyst mixture, wherein the weight ratio of rare earth carbonate: catalyst: porous silicon is in the range of 1-5:1-5:100; preferably, in this step S20), the weight proportion of rare earth carbonate in the rare earth carbonate aqueous solution is not less than 0.5wt%, preferably 1-10wt%; the rare earth carbonate is selected from one of lanthanum carbonate, cerium carbonate, yttrium carbonate, praseodymium carbonate or a mixture of any of them; the catalyst aqueous solution The weight percentage of the catalyst in the liquid is not less than 0.5wt%, preferably 1-10wt%; the catalyst is selected from one of ferric chloride, cobalt chloride, and nickel chloride or a mixture of any of them; further preferably, in order to ensure the uniformity of the dispersion of the porous silicon-rare earth-catalyst mixture and facilitate good doping and recombination during the subsequent hydrothermal reaction, the porous silicon-rare earth-catalyst mixture is also added with melamine accounting for not less than 0.2wt% (preferably not less than 0.5wt%, more preferably 0.5-2wt%) of the weight percentage thereof, and ultrasonic dispersion is used for uniformity;
[0027] S30), subjecting the porous silicon-rare earth-catalyst mixture to a hydrothermal reaction under heating and pressurizing conditions to obtain a rare earth-doped silicon-based material precursor; preferably, in this step S30), the heating and pressurizing conditions are set to: react at a temperature range of 100-250°C and a pressure range of 1-5Mpa for at least 1 hour (preferably 1-6 hours), and after the hydrothermal reaction is completed, the reaction product is filtered and freeze-dried to obtain a rare earth-doped silicon-based material precursor; in the specific implementation, the nitrogen source and the carbon source are deposited and coated in sequence or simultaneously by vapor deposition; further Preferably, the nitrogen source and the carbon source are deposited and coated in sequence by vapor deposition; further preferably, in this embodiment, the nitrogen source is 3-aminopropyltriethoxysilane gas, which is kept warm at a temperature range of 900-1300°C for at least 1 hour (preferably 1-3 hours), and the 3-aminopropyltriethoxysilane gas undergoes a cracking reaction, so that the surface of the rare earth-doped silicon-based material precursor is deposited and coated with the nitrogen source; the carbon source is a carbon source gas (any known carbon source gas can be selected) which is kept warm at a temperature range of 700-1100°C for at least 1 hour (preferably 1-3 hours).
[0028] It should be noted that the present application has illustrated various priority range parameters through the above embodiments through a large number of experiments. Those skilled in the art can choose within these preferred parameter ranges (including endpoint values and intermediate values) according to actual conditions. In order to save the length of the specification, the present embodiments will not be expanded one by one.
[0029] Preferably, this embodiment further proposes a multi-element doped silicon-based composite material, which is obtained by the preparation method described above in this embodiment.
[0030] Preferably, this embodiment also proposes an application of the multi-element doped silicon-based composite material as described above, and the multi-element doped silicon-based composite material is used as an active material raw material for preparing battery pole pieces; specifically, it can be used as a battery negative electrode sheet, which can be selected according to actual requirements; in the specific implementation, the process for preparing the battery negative electrode sheet can adopt any known process, which does not belong to the innovative content of this application, and this application does not impose any restrictions on it; it should also be noted that when the present application is implemented, the battery can be a button battery, a soft-pack battery or other well-known batteries, and technical personnel in this field can apply it according to actual needs, and this application does not impose any special restrictions on this.
[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0032] Example 1: Perform the following steps:
[0033] (1) placing an aluminum silicon alloy (silicon content of 80 wt%, sieved through 300 mesh) in a heating dish, heating hydrofluoric acid to a vapor state, etching its surface for 6 hours, and then washing with deionized water to obtain porous silicon; adding 3 g of cerium carbonate to 60 ml of deionized water to prepare a cerium carbonate aqueous solution with a concentration of 5 wt%; adding 3 g of ferric chloride to 60 ml of deionized water to prepare a ferric chloride solution with a concentration of 5 wt%;
[0034] (2) 100 g of porous silicon, cerium carbonate solution and ferric chloride solution obtained in step (1) are mixed evenly, and 1 g of melamine is added to obtain a porous silicon-rare earth-catalyst mixture by ultrasonic dispersion;
[0035] (3) transferring the porous silicon-rare earth-catalyst mixture into a high-pressure reactor, reacting it at a temperature of 150° C. and a pressure of 3 MPa for 3 hours, then filtering it and freeze-drying it at a low temperature of -40° C. for 24 hours to obtain a rare earth-doped silicon-based material precursor;
[0036] (4) The rare earth-doped silicon-based material precursor is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then 3-aminopropyltriethoxysilane gas is introduced. The temperature is kept at 1100°C for 2 hours, and then methane carbon source gas is introduced. The temperature is kept at 900°C for 2 hours, and then the temperature is cooled to room temperature in an argon inert atmosphere and crushed to obtain a rare earth / nitrogen-doped silicon-based material, that is, a multi-element doped silicon-based composite material.
[0037] The present application conducted a SEM (scanning electron microscope) test on the multi-element doped silicon-based composite material obtained in Example 1. The test results are as follows: Figure 1 As shown, we pass Figure 1 It can be seen that the multi-element doped silicon-based composite material obtained in Example 1 presents a granular structure, with a small amount of doping substances on the surface, and the particle size is between 5-10 μm.
[0038] Example 2: Perform the following steps:
[0039] (1) A magnesium silicon alloy (silicon content of 80 wt%, sieved through 300 mesh) was placed in a heating dish, and hydrofluoric acid was heated to a vapor state, and its surface was etched for 1 hour, followed by washing with deionized water to obtain porous silicon; 1 g of lanthanum carbonate was added to 100 ml of deionized water to obtain a lanthanum carbonate aqueous solution with a concentration of 1 wt%; 1 g of cobalt chloride was added to 100 ml of deionized water to obtain a cobalt chloride solution with a concentration of 1 wt%;
[0040] (2) 100 g of porous silicon, lanthanum carbonate solution and cobalt chloride solution obtained in step (1) are mixed evenly, and 0.5 g of melamine is added to obtain a porous silicon-rare earth-catalyst mixture by ultrasonic dispersion;
[0041] (3) transferring the porous silicon-rare earth-catalyst mixture into a high-pressure reactor, reacting it at a temperature of 100° C. and a pressure of 5 MPa for 6 hours, then filtering it and freeze-drying it at a low temperature of -40° C. for 24 hours to obtain a rare earth-doped silicon-based material precursor;
[0042] (4) The rare earth-doped silicon-based material precursor is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then 3-aminopropyltriethoxysilane gas is introduced. The temperature is kept at 900°C for 3 hours, and then ethylene carbon source gas is introduced. The temperature is kept at 700°C for 3 hours, and then the temperature is cooled to room temperature in an argon inert atmosphere and crushed to obtain a rare earth / nitrogen-doped silicon-based material, that is, a multi-element doped silicon-based composite material.
[0043] Example 3: Perform the following steps:
[0044] (1) Place a nickel-silicon alloy (silicon content of 80 wt%, sieved through 300 mesh) in a heating dish, heat hydrofluoric acid to a steam state, etch its surface for 12 hours, and then wash with deionized water to obtain porous silicon; add 5 g of yttrium carbonate to 50 ml of deionized water to prepare an aqueous solution of yttrium carbonate with a concentration of 10 wt%; add 5 g of nickel chloride to 50 ml of deionized water to prepare a nickel chloride solution with a concentration of 10 wt%;
[0045] (2) 100 g of porous silicon, yttrium carbonate solution and nickel chloride solution obtained in step (1) are mixed evenly, and 2 g of melamine is added to obtain a porous silicon-rare earth-catalyst mixture by ultrasonic dispersion;
[0046] (3) transferring the porous silicon-rare earth-catalyst mixture into a high-pressure reactor, reacting it at a temperature of 250° C. and a pressure of 1 MPa for 1 hour, then filtering it and freeze-drying it at a low temperature of -40° C. for 24 hours to obtain a rare earth-doped silicon-based material precursor;
[0047] (4) The rare earth-doped silicon-based material precursor is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then 3-aminopropyltriethoxysilane gas is introduced. The temperature is kept at 1300°C for 1 hour, and then acetylene carbon source gas is introduced. The temperature is kept at 1100°C for 1 hour, and then the temperature is cooled to room temperature in an argon inert atmosphere and crushed to obtain a rare earth / nitrogen-doped silicon-based material, that is, a multi-element doped silicon-based composite material.
[0048] In order to verify the technical effects achieved by the embodiments of the present application, the present application also specially sets up the following comparative examples:
[0049] Comparative Example 1: Operate according to the following steps:
[0050] (1) placing an aluminum silicon alloy (silicon content of 80 wt%, sieved through 300 mesh) in a heating dish, heating hydrofluoric acid to a steam state, etching its surface for 6 hours, and then washing with deionized water to obtain porous silicon;
[0051] (2) The porous silicon is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then 3-aminopropyltriethoxysilane gas is introduced. The temperature is kept at 1100°C for 2 hours, and then methane carbon source gas is introduced. The temperature is kept at 900°C for 2 hours, and then the temperature is cooled to room temperature in an argon inert atmosphere, and the tube is crushed to obtain a silicon-based composite material.
[0052] Comparative Example 2: The rest of the technical solutions of Comparative Example 2 are the same as those of Example 1, except that, in Comparative Example 2, nano-silicon with an average particle size not higher than 2 μm is used to replace the aluminum-silicon alloy in Example 1.
[0053] Comparative Example 3: The rest of the technical solutions of this Comparative Example 3 are the same as those of Example 1, except that, in this Comparative Example 3, the surface etching treatment of the aluminum-silicon alloy is omitted, and 100 g of aluminum-silicon alloy (silicon content is 80 wt %, sieved through 300 mesh) is directly used to replace the 100 g of porous silicon in step (2).
[0054] Comparative Example 4: The remaining technical solutions of this comparative example 4 are the same as those of Example 1, except that, in this comparative example 4, step (4) in Example 1 is replaced by:
[0055] The rare earth-doped silicon-based material precursor is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then 3-aminopropyltriethoxysilane gas is introduced. The temperature is kept at 1100°C for 2 hours, and then the temperature is cooled to room temperature in an argon inert atmosphere and crushed to obtain a silicon-based composite material.
[0056] Comparative Example 5: The remaining technical solutions of this comparative example 5 are the same as those of Example 1, except that, in this comparative example 5, step (4) in Example 1 is replaced by:
[0057] The rare earth-doped silicon-based material precursor is transferred to a tubular furnace, and argon inert gas is first introduced to expel the air in the tube, and then methane carbon source gas is introduced. The temperature is kept at 900°C for 2 hours, and then the temperature is cooled to room temperature in an argon inert atmosphere and crushed to obtain a silicon-based composite material.
[0058] In order to compare and verify the effects of the above embodiments and comparative examples, the present application uses the silicon-based composite materials obtained in the above embodiments 1-3 and comparative examples 1-5 as active material raw materials for negative electrode materials of lithium-ion batteries, and assembles them by the following methods to obtain 8 button batteries, which are respectively recorded as A1, A2, A3, B1, B2, B3, B4, and B5:
[0059] A binder, a conductive agent and a solvent are added to the corresponding silicon-based composite material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet, wherein the binder used is LA132, the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), and the amount ratio of the silicon-based composite material, SP, LA132, and NMP is 95g:1g:4g:220mL; a metal lithium sheet is used as a counter electrode, a polypropylene (PP) film is used as a diaphragm, LiPF6 is used as an electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 is used as a solvent; the button battery is assembled in an argon-filled glove box.
[0060] The present application conducted electrochemical performance tests on the button batteries prepared in the above embodiments 1-3 and comparative examples 1-5, respectively. The electrochemical performance tests were specifically carried out on a Wuhan Blue Electric CT2001A battery tester, and the charge and discharge conditions used in the test were: the charge and discharge voltage range was 0.005V-2.0V, and the charge and discharge rate was 0.1C.
[0061] The test results are shown in Table 1 below:
[0062] Table 1
[0063]
[0064] It can be seen from the data in Table 1 that the specific capacity and the first efficiency of the rare earth / nitrogen doped silicon-based materials prepared in Examples 1-3 of the present invention are significantly better than those in Comparative Examples 1-5. The reason may be that: the present invention improves the electronic conductivity of the silicon-based material by doping rare earth metals in its porous silicon, reduces the internal resistance and thus improves the specific capacity of the material and its first efficiency; at the same time, the amorphous carbon formed by the doped catalyst during its carbonization process has the advantages of good isotropy and the like, which can effectively reduce the impedance.
[0065] In order to compare and verify the effects of the above embodiments and comparative examples, the present application also uses the silicon-based composite materials obtained in the above embodiments 1-3 and comparative examples 1-5 as the active material raw material of the negative electrode material of the lithium ion battery, and assembles them by the following method to obtain 8 soft-pack batteries with a specification of 5Ah. According to the order of embodiment 1, embodiment 2, embodiment 3 and comparative example 1, comparative example 2, comparative example 3, comparative example 4, comparative example 5, the corresponding soft-pack batteries prepared are marked as C1, C2, C3 and D1, D2, D3, D4, D5 respectively:
[0066] The negative electrode sheet was prepared by doping 90wt% (percentage by weight of the negative electrode sheet) of artificial graphite into its corresponding silicon-based composite material as the negative electrode material, using NCM532 as the positive electrode material, Celgard 2400 membrane as the separator, LiPF6 as the electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 as the solvent, and the concentration of LiPF6 was 1.3mol / L; a 5Ah soft-pack battery was prepared.
[0067] First, the present application conducted the following performance tests on the negative electrode sheets prepared in the above Examples 1-3 and Comparative Examples 1-5, respectively. The test results are shown in Tables 2 and 3 below:
[0068] A. Liquid absorption capacity test: Use a 1mL burette and absorb VmL of electrolyte, add a drop on the surface of the negative electrode, and time it until the electrolyte is completely absorbed. Record the required time t and calculate the liquid absorption rate V / t of the electrode.
[0069] B. Liquid retention rate test: Calculate the theoretical liquid absorption of the negative electrode m1 according to the negative electrode parameters, and weigh the weight of the electrode m2. Then, place the negative electrode in the electrolyte and soak it for 24 hours. Weigh the weight of the negative electrode as m3, calculate the liquid absorption of the negative electrode = m3-m2, and calculate the liquid retention rate according to the following formula:
[0070] Liquid retention rate = (m3-m2)*100% / m1.
[0071] Table 2
[0072]
[0073] It can be seen from Table 2 above that when the silicon-based composite materials prepared in Examples 1-3 of the present invention are used as active material raw materials for battery negative electrode sheets, the liquid absorption and liquid retention capabilities of the negative electrode sheets are significantly higher than those of Comparative Examples 1-5. The experimental results show that the negative electrode sheets prepared using the multi-element doped silicon-based composite materials provided by the present invention have higher liquid absorption and liquid retention capabilities.
[0074] C. Electrode rebound rate test: First, use a thickness gauge to test the average thickness of the negative electrode sheet as D1. Then place the negative electrode sheet in a vacuum drying oven at 80°C for 48 hours. The thickness of the negative electrode sheet is tested as D2, and the rebound rate is calculated according to the following formula:
[0075] Rebound rate = (D2-D1)*100% / D1.
[0076] D. Electrode resistivity test: Use a resistivity tester to test the resistivity of the electrode.
[0077] Table 3
[0078] Electrode rebound rate (%) Electrode sheet resistivity (mΩ) Example 1 8.8 16.8 Example 2 9.6 17.9 Example 3 10.1 20.1 Comparative Example 1 19.6 328.5 Comparative Example 2 9.8 241.5 Comparative Example 3 20.5 276.7 Comparative Example 4 11.5 387.9 Comparative Example 5 10.3 256.4
[0079] It can be seen from Table 3 above that when the silicon-based composite materials prepared in Examples 1-3 of the present invention are used as active material raw materials for battery negative electrode sheets, the rebound rate and resistivity of the negative electrode sheets are significantly lower than those in Comparative Examples 1-5. The reason may be that the doped rare earth elements in Examples 1-3 reduce the impedance, and the mesh-like unoriented carbon-bound silicon-based core material is coated in the outer shell, and the expansion during the charge and discharge process and the rolling process can effectively reduce the rebound of the electrode sheet.
[0080] Then, the present application conducted the following performance tests on the soft-pack batteries prepared in the above Examples 1-3 and Comparative Examples 1-5, respectively. The test results are shown in Table 4 below:
[0081] E. Cycle performance test: The charge and discharge conditions adopted are: the charge and discharge rate is 1C / 1C, the voltage range is 2.8V-4.2V, and the cycle performance of the battery is tested at a temperature of 25±3℃.
[0082] F. Fast charging performance test: Perform constant current + constant voltage charging at a rate of 3C, with a cut-off voltage of 4.2V, and calculate the constant current ratio, where constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity).
[0083] Table 4
[0084]
[0085] It can be seen from Table 4 that when the silicon-based composite materials prepared in Examples 1-3 of the present invention are used as the active material raw material of the negative electrode of the battery, the cycle performance and fast charging performance (constant current ratio) of the prepared battery are significantly better than those of Comparative Examples 1-5; the reason may be that: the electrode prepared by using the multi-element doped silicon-based composite material provided by the present invention has a lower expansion rate, and the structure of the electrode is more stable during the charging and discharging process, thereby improving its cycle performance; in addition, by reducing the impedance by doping low-impedance elements such as rare earth and nitrogen, the constant current ratio of the battery can be significantly improved.
[0086] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0087] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a multi-element doped silicon-based composite material, characterized in that: Rare earth and catalyst are doped into porous silicon through hydrothermal reaction to obtain a rare earth-doped silicon-based material precursor as a core; then nitrogen source and carbon source are deposited and coated on the surface of the rare earth-doped silicon-based material precursor by vapor deposition; the catalyst is selected from one of ferric chloride, cobalt chloride, nickel chloride or a mixture of any of them.
2. The preparation method according to claim 1, characterized in that: The steps of preparing the rare earth-doped silicon-based material precursor include: S10), etching the surface of the silicon alloy with acid vapor to obtain porous silicon; S20), uniformly mixing the porous silicon obtained in the above step S10) with a rare earth carbonate aqueous solution and a catalyst aqueous solution to obtain a porous silicon-rare earth-catalyst mixture, wherein the weight ratio of rare earth carbonate: catalyst: porous silicon is in the range of 1-5:1-5:100; S30), subjecting the porous silicon-rare earth-catalyst mixture to a hydrothermal reaction under heating and pressurization conditions to obtain the rare earth-doped silicon-based material precursor.
3. The preparation method according to claim 2, characterized in that: In the step S10), the silicon alloy is selected from one of aluminum silicon alloy, magnesium silicon alloy, nickel silicon alloy, titanium silicon alloy, tungsten silicon alloy or a mixture of any of them, wherein the silicon content in the silicon alloy is not less than 60wt%; the acid vapor is hydrofluoric acid vapor, and the etching time is not less than 1 hour.
4. The preparation method according to claim 2, characterized in that: In the step S20), the weight proportion of rare earth carbonate in the rare earth carbonate aqueous solution is not less than 0.5wt%; the rare earth carbonate is selected from one of lanthanum carbonate, cerium carbonate, yttrium carbonate, and praseodymium carbonate, or a mixture of any of them.
5. The preparation method according to claim 2, characterized in that: In the step S20), the weight proportion of the catalyst in the catalyst aqueous solution is not less than 0.5 wt %.
6. The preparation method according to claim 2, 4 or 5, characterized in that: In the step S20), the porous silicon-rare earth-catalyst mixture is further added with melamine accounting for no less than 0.2 wt % of the weight of the porous silicon-rare earth-catalyst mixture, and is evenly dispersed by ultrasonication.
7. The preparation method according to claim 2, characterized in that: In the step S30), the heating and pressurizing conditions are set as: reacting at a temperature range of 100-250°C and a pressure range of 1-5Mpa for at least 1 hour, filtering the reaction product after the hydrothermal reaction is completed, and performing low-temperature freeze-drying to obtain the rare earth-doped silicon-based material precursor.
8. The preparation method according to claim 1, characterized in that: The nitrogen source and the carbon source are deposited and coated sequentially or simultaneously by a vapor deposition method.
9. The preparation method according to claim 1, characterized in that: The nitrogen source is 3-aminopropyltriethoxysilane gas, which is kept warm at a temperature range of 900-1300°C for at least 1 hour, and the 3-aminopropyltriethoxysilane gas undergoes a cracking reaction, so that the surface of the rare earth-doped silicon-based material precursor is deposited and coated with the nitrogen source; and / or the carbon source is carbon source gas, which is kept warm at a temperature range of 700-1100°C for at least 1 hour.
10. A multi-element doped silicon-based composite material, characterized in that: The method is as described in any one of claims 1 to 9.
Citation Information
Patent Citations
A ternary doped silicon-based composite material, its preparation method and application
CN111048770B
Anode slurry for secondary battery
CA3043254A1
Method for in-situ growth of carbon nanotube from silicon or oxide thereof
CN111799448A